Responding To Globalization’s Impact On Local Communities: Preparing For Global Tourism Expansion In Cuba - González Herrera, Manuel Ramón; Spiegel, Jerry (Advances in Social Sciences Research Journal, 2017)
This paper explores how the concept of resistance can be incorporated for understanding the effects of globalization on local communities in order to strengthen capacities for optimizing benefits and mitigating negative effects. The paper describes how the hierarchy of institutional, economic, social-cultural and ecological factors that can produce local impacts can accordingly serve as the basis for monitoring as well as for developing policy options in support of identified values and concerns, bringing together a range of disciplinary and stakeholder perspectives. Using a case study conducted in a Cuban coastal community potentially vulnerable to effects of global tourism expansion, the application of this approach is introduced as a way to link producers and users of relevant population information. In light of increased awareness of the impact of adverse potential effect of community restructuring associated with the global expansion of tourism merits attention. In the context of the potential population health implications of tourism expansion the challenge that emerges is not merely to better identify the risks and threats that constitute pathways that can lead to local health effects, but to consider options for mitigating negative impacts and taking advantage of positive opportunities. While Cuba is in many ways unique, the approach described above can provide valuable lessons to the international community in navigating a course between the allure of tourism dollars and the health and well-being of local populations.